Penatalaksanaan Fisioterapi Pada Kasus Ischialgia Sinistra Di Rsud Dr. Soehadi Prijonegoro Sragen - Nurwindita, Nadia Fatma; , Dwi Kurniawati, S.ST.,FT.,M.Kes (2016)
Background: Ischialgia is a condition where there is pain, weakness, burning sensation and tingling along the back of the foot (along persyarafan Ischiadicus) caused by compression or accident. Ischialgia attack Ischiadicus nerves originating from the posterior root L4-S3. Physiotherapy modalities with Infra Red (IR) and Transcutaneous Electrical Nerve Stimulation (TENS) used were to block pain or relieve pain. And Therapeutic Exercises with William Flexion Exercise method can be useful in maintain or increase range of motion and improving muscle strength. Purpose: To study about physiotherapy management in reducing pain, maintain or increase range of motion and improving muscle strength in the case of Ischialgia Sinistra using modalities Infra Red (IR), Transcutaneous Electrical Nerve Stimulation (TENS) and Therapeutic Exercises. Results: After therapy for about 6 times the obtained results of the assessment of pain in silent pain T0 : 3 to T6 : 1, tenderness T0 : 4 to T6 : 2, motion pain T0 : 5 to T6 : 3. Increased functional scope trunk motion in flexion T0 : 7 cm to T6 : 11 cm, extension T0 : 4 cm to T6 : 5 cm, side flexion right T0 : 14 cm to T6 : 14 cm, side flexion left T0 : 15 cm to T6 : 15 cm. Increased muscle strength trunk flexor T0 : 4 to T6 : 5, extensor T0 : 4 to T6 : 4. Increased muscle strength hip on flexor T0 : left 3 to T6 : left 4, extensor T0 : left 4 to T6 : left 4, abductor T0 : left 3 to T6 : left 4, adductor T0 : left 4 to T6 : left 4, exorotatator T0 : left 4 to T6 : left 4, endorotator T0 : left 5 to T6 : left 5. Conclusion: Infra Red (IR), Transcutaneous Electrical Nerve Stimulation (TENS) and Therapeutic Exercise can reduce pain, increase range of motion and improving muscle strength.